FINANCIAL INCLUSION : KEY ROLE OF INDIAN BANKING SECTOR (International Journal of Food and Nutritional Sciences, 2021)
Exclusion from formal finance led to exploitation, lack of confidence, confiscation of collateral, slavery in case of non-repayment, and lack of opportunities for gainful employment and so on. This necessitates inclusion of hither to financially excluded section of marginalized people into formal financial sector. There is no equal opportunity to everyone to grow and flourish. Though market liberalization and globalization create new opportunities for rapid growth, relative poverty, economic and regional disparities have tended to widen. This situation demands Inclusive growth and financial inclusion for participatory development of the society.As a solution to the problem of exclusion, the concept ‘Inclusive Growth’ gained enormous importance. Inclusive growth is nothing but economic growth with more inclusion providing each and everyone to participate in and benefit from the growth activities. Financial inclusion is a powerful tool for achieving inclusive growth. It refers to the provision of affordable financial services including access to savings, loans, overdraft facility, payment and remittance facilities, financial advice and insurance services to vast sections of low income groups and disadvantaged. It helps to uplift the poor from the clutches of poverty and also to reduce the widening gap between poor and rich